The Concept of Philosophy in Post-Apartheid Western Historical Overviews of South African Old Testament Scholarship - Gericke, Jaco (Old Testament Essays, 2018)
This article seeks to clarify the concept of “philosophy” as it appeared within popular overviews of South African Old Testament scholarship published in the post-apartheid era. After providing a typology of related research, the discussion proceeds with the identification of the words “philosophy”/“philosophical” in the associated colonialist scholarly discourses. The latter part involves a brief classification, commentary and critique of the meta-philosophical assumptions supervening on the associated intra- and cross-disciplinary contexts.